The impact of self-directed team on high-performance organization with the mediating role of knowledge sharing culture: Organizational support as a moderator - Mohammed, Bakr Fakhri; Jingjie, Zhao; Yang, Cong; Yuwei, You; Ali Attia Zalat, Yousra Mahmoud (Frontiers in Psychology, 2022)
The primary aim of this investigation is to identify the relationship between self-directed teams and high-performance organizations (work). Furthermore, exploring the mediating role of knowledge-sharing culture with the self-directed team and high-performance organization relationships. Moreover, this study analyzed the moderating role of a sense of organizational support in the relationship between knowledge-sharing culture and high-performance organizations. Using the PLS-SEM approach (SmartPLS 3.3.7) in this study, we obtained data from employees of high-tech enterprises listed on the Shanghai Stock Exchange China to analyze this study. The present research seeks to determine the direct and indirect effects of the study-related factors on the outcome of the investigation. According to the findings, a self-directed team positively impacts knowledge sharing culture, knowledge sharing behavior, knowledge sharing strategy, and mutual trust among its members. Knowledge-sharing culture has no mediating role and its component in the relationship between independent and dependent constructs. This study also indicated that a sense of organizational support has no moderating effect on the relationship between a knowledge-sharing culture and high-performance organizations. This study may practically contribute to high-tech enterprises to develop and implement business development and proper self-directed team, knowledge-sharing culture, and sense of organizational support, and consequently, can contribute to the growth of overall high-performance organizations.